Effect of Ball Milling Treatment on Thermal, Structural, and Morphological Properties of Phosphated Starches from Corn and Pinhão - Beninca, Cleoci; de Oliveira, Cristina Soltovski; Bet, Camila Delinski; Bisinella, Radla Zabian Bassetto; Gaglieri, Caroline [UNESP]; Schnitzler, Egon (Wiley, 2020)
In the previous study, the effect of chemical modification with sodium tripolyphosphate on the properties of corn and pinhão starches was evaluated. However, physical modifications also confer specific characteristics on the starch, diversifying its application. Thus, in this study, thermal (thermogravimetry [TG], differential exploratory calorimetry [DSC]), structural (X-ray powder diffractometry [XRD], Fourier-transform infrared [FTIR]) and morphological (field emission gun-scanning electron microscopy) properties of native and phosphated corn and pinhão starches are evaluated before and after ball milling treatment. In addition, wavelength dispersive X-ray spectroscopy is applied as a new technique to measure the level of phosphorus and sodium. The incorporation of phosphate groups in starches is confirmed and phosphorus and sodium are reduced after milling. The doubly modified starches show lower moisture retention capacity and lower thermal stability. All treatments reduce the gelatinization enthalpy mainly for double modified starches. Relative crystallinity is drastically reduced after the double modification. Changes in FTIR results are more pronounced after the physical treatment, corroborating with DSC and XRD results. Morphological changes are observed only in the milled samples. Thus, the double modification confer greater changes compared to the isolated modifications.
Keywords: Araucaria angustifolia; phosphated starch; physical modification